We're Going The Same Way - Damme, Van Pieter-Jan (Belgium, 2018)
A father and son share simple dreams and a lifetime on the road. Along an unromantic silk route, Seragedin and his son Rakhman choose to live an honest life to make their dreams come true.
Verzio Film Festival Submission
Keywords: Documentary films